Revisiting Al-Jaww: Exploring the Sacred Landscape of a Volcanic Cult Site In Northwestern Saudi Arabia - Dunn, Jacob E. (Antiguo Oriente, 2024)
Located in between Harrat ar-Rahah and Harrat al-‘Uwayrid in Northwestern Saudi Arabia lies an erosional depression known as al-Jaww, where Hallat al-Badr, a geologically young Holocene epoch cinder cone volcano, sits atop a massive sandstone and lava plateau called Jabal Thadra. The Thadra plateau is located approximately 115 km northwest of al-Ula, the capital of the ancient Dedanite kingdom, and is directly situated along the Darb al-Bakrah caravan route. After an exhaustive search through the literature on this remote region of northwestern Saudi Arabia, very little is known about al-Jaww and Hallat al-Badr’s eruptive history, the age of the stone monuments and rock art in its vicinity, the ancient people groups that frequented this region, and the mountain’s larger role in the cultic landscape of northwest Arabia. This article takes an interdisciplinary approach and provides a preliminary geographical, geological, and archaeological analysis of this region, making the case that Jabal Thadra was a cultic “high place” for local nomadic tribes.